The weather makers : the history and future impact of climate change - Flannery, Tim F. (Tim Fridtjof), 1956- (New York : Atlantic Monthly Press, 2006)
A history of climate change, how it will unfold over the next century, and what we can do to prevent a cataclysmic future includes specific suggestions for both lawmakers and individuals.
Keywords: Climatic changes; Global warming